The Effect of Digital Payments on Financial Inclusion in Rural West Java - Nagara, Agung Satya; Sukaryono, Adilaksana; Sukresna, I Made (LifeSciFi, 2024)
In today's digital era, financial inclusion is one of the main challenges, especially in rural areas of Indonesia, which still face limited access to financial services. With only 70.13% of the rural population financially included, many people remain dependent on the informal sector, which often falls short of meeting optimal financial needs. Amid these challenges, digital payment technology emerges as a promising solution to bridge the financial access gap. This study examines the impact of digital payments on financial inclusion in rural West Java, using a quantitative survey method through questionnaires distributed to digital payment users. The analysis results indicate that the use of e-wallets and QR payments significantly increases community access to financial products and services. This research provides valuable insights for policymakers and stakeholders in designing more effective strategies to enhance financial inclusion in rural areas, thereby promoting economic growth and overall community well-being.